Linking economic and digital indicators to human development: Evidence from eastern Indonesia - Devi Andini; Herlitah Herlitah; Aditya Pratama (Journal of Economics Research and Policy Studies, 2025)
This study aims to analyze the effect of the Provincial Minimum Wage (UMP), Gross Regional Domestic Product (GRDP), and the Information and Communication Technology Development Index (ICT-Dev Index) on the Human Development Index (HDI) in Eastern Indonesia. This research employs a quantitative approach with panel data regression analysis. The study uses secondary panel data from 13 provinces in Eastern Indonesia for the period 2019–2023, obtained from Statistics Indonesia (BPS) and the Ministry of Manpower of the Republic of Indonesia. The results show that the UMP has a positive and significant effect on HDI, GRDP has a negative and insignificant effect on HDI, while the ICT-Dev Index has a positive and significant impact on HDI. Simultaneously, UMP, GRDP, and the ICT-Dev Index have a positive and significant effect on HDI. The coefficient of determination indicates that 99.01% of the variation in HDI can be explained by UMP, GRDP, and the ICT-Dev Index, while the remaining 0.99% is influenced by other factors not examined in this study.